Deep sequencing in CD34+ cells from peripheral blood enables sensitive detection of measurable residual disease in AML - Stasik, Sebastian; Burkhard-Meier, Clara; Kramer, Michael; Middeke, Jan M.; Oelschlaegel, Uta; Sockel, Katja; Ehninger, Gerhard; Serve, Hubert; Müller-Tidow, Carsten; Baldus, Claudia D.; Röllig, Christoph; Bornhäuser, Martin; et al. (Blood advances, 2022)
Monitoring of measurable residual disease (MRD) in patients with acute myeloid leukemia (AML) is predictive of disease recurrence and may identify patients who benefit from treatment intensification. Current MRD techniques rely on multicolor flow cytometry or molecular methods, but are limited in applicability or sensitivity. We evaluated the feasibility of a novel approach for MRD detection in peripheral blood (PB), which combines immunomagnetic preenrichment and fluorescence-activated cell sorting (FACS) for isolation of CD34+ cells with error-reduced targeted next-generation sequencing (NGS). For clinical validation, we retrospectively analyzed 429 PB and 55 bone marrow (BM) samples of 40 patients with AML or high-risk MDS, with/without molecular relapse based on CD34+ donor chimerism (DC), in complete remission after allogeneic stem cell transplantation. Enrichment of CD34+ cells for NGS increased the detection of mutant alleles in PB ∼1000-fold (median variant allele frequency, 1.27% vs 0.0046% in unsorted PB; P < .0001). Although a strong correlation was observed for the parallel analysis of CD34+ PB cells with NGS and DC (r = 0.8601), the combination of FACS and NGS improved sensitivity for MRD detection in dilution experiments ∼10-fold to levels of 10−6. In both assays, MRD detection was superior using PB vs BM for CD34+ enrichment. Importantly, NGS on CD34+ PB cells enabled prediction of molecular relapse with high sensitivity (100%) and specificity (91%), and significantly earlier (median, 48 days; range, 0-281; P = .0011) than by CD34+ DC or NGS of unsorted PB, providing additional time for therapeutic intervention. Moreover, panel sequencing in CD34+ cells allowed for the early assessment of clonal trajectories in hematological complete remission.